ASEAN and KOREA Emerging Issues in Trade and Investment Relations - Singh, Daljit; Siregar, Reza Yamora (ISEAS Publishing, 1995)
Trade and investment linkages between Northeast and Southeast Asia have been widening and deepening over the last two decades, helping to integrate the East Asian and Asian Pacific regions. More recently, security linkages have been developing. Much of the scholarly attention has understandably focused on the role of Japan in this integration. Yet the role of the Northeast Asian NIEs since the 1980s has become increasingly important. In this volume scholars from Korea and the ASEAN countries look at the issues arising from trade and investment interactions between Korea and the ASEAN region which have grown enormously over the past decade. It provides a wealth of data and the unique perspective of east ASEAN country and Korea. While the focus is economics some of the political dimensions have also been included